Effect of microstructure on electrical conductivity of Inconel 718 alloys. (April 2015) - Pereira, D.; Clarke, T.; Menezes, R.; Hirsch, T.
<x content-type="archive" xml:space="preserve">Abstract</x> The microstructural evolution of Inconel 718 during aging processes has been studied through a combination of eddy current testing, X-ray diffraction analysis, and metallography and hardness measurements. Measurements were carried out in samples subjected to eight different heat treatment cycles, between 620 and 1035°C for 1–18 h. Different amounts of secondary precipitates were achieved, reaching 18% of delta phase for samples overaged at 900°C for 18 h. Results show that the different microstructures of Inconel 718 obtained have a distinguishable effect on electrical conductivity when this is measured through an appropriately sensitive technique (i.e. eddy current testing). The lowest conductivity values were observed for under aged samples (1·44% IACS). A clear increase in conductivity values was seen for all aged or overaged conditions, reaching a maximum of 1·63% IACS, when coarsening of intra granular precipitates, associated with an increase in density of globular precipitates at grain boundaries, was identified. The influence of microstructure on conductivity could be shown to be due to the competition between two effects on the scattering of electrons: matrix purification and precipitation characteristics. A combination of hardness values and electrical properties proved to be a fast and practical way of determining the stage of aging of the alloy.